Ethnoarchaeological fieldwork in Zimbabwe: people, pots, structures and scientific mementoes - Huffman, Thomas (Southern African Humanities, 2019)
In the 1970s, I began an ethnoarchaeological study into types of structures, pottery and population numbers in rural areas of Rhodesia (Zimbabwe). This study extended to every major linguistic cluster in Zimbabwe, including Kalanga and Matabele, and provided a background to different macro-identities in the material-culture record. In the process, I acquired various ‘scientific mementoes’ for my personal use. These mementoes ranged from axes, beadwork and pottery to doors, drums, thumb pianos and ritual objects. Here I provide some background to Tonga and Korekore items collected from the Zambezi Valley, as well as from Central Shona in the Runde and Buhera areas and Ndau villages near Chikore Mission. The larger project encompassing these diverse areas had three goals: to clarify excavated features uncovered at Great Zimbabwe and Leopard’s Kopje Main Kraal; to estimate prehistoric populations based on the ratio of structures to people; and to record different ceramic traditions. At the time, the minimum household throughout the country comprised a kitchen, sleeping room and granary. Although low, a ratio of four people per household provides an average for estimating prehistoric populations. For ceramics, collections were sufficient for stylistic analyses but because of modern market forces, frequencies of functional types are not relevant to archaeological assemblages. Even so, these field data help to elucidate the human context for the kind of pottery fragments archaeologists often study. Conclusions such as these informed later research but original field data appear here for the first time. KEY WORDS: Ethnoarchaeology, Ndebele, Shona, Tonga, traditional material culture.